summary |
shortlog |
changelog |
graph |
tags |
bookmarks |
branches |
files |
changeset |
file |
latest |
revisions |
annotate |
diff |
comparison |
raw |
help

src/Sequents/T.thy

author | wenzelm |

Sat, 13 Mar 2010 16:44:12 +0100 | |

changeset 35762 | af3ff2ba4c54 |

parent 30549 | d2d7874648bd |

child 39159 | 0dec18004e75 |

permissions | -rw-r--r-- |

removed old CVS Ids;
tuned headers;

(* Title: Sequents/T.thy Author: Martin Coen Copyright 1991 University of Cambridge *) theory T imports Modal0 begin axioms (* Definition of the star operation using a set of Horn clauses *) (* For system T: gamma * == {P | []P : gamma} *) (* delta * == {P | <>P : delta} *) lstar0: "|L>" lstar1: "$G |L> $H ==> []P, $G |L> P, $H" lstar2: "$G |L> $H ==> P, $G |L> $H" rstar0: "|R>" rstar1: "$G |R> $H ==> <>P, $G |R> P, $H" rstar2: "$G |R> $H ==> P, $G |R> $H" (* Rules for [] and <> *) boxR: "[| $E |L> $E'; $F |R> $F'; $G |R> $G'; $E' |- $F', P, $G'|] ==> $E |- $F, []P, $G" boxL: "$E, P, $F |- $G ==> $E, []P, $F |- $G" diaR: "$E |- $F, P, $G ==> $E |- $F, <>P, $G" diaL: "[| $E |L> $E'; $F |L> $F'; $G |R> $G'; $E', P, $F'|- $G'|] ==> $E, <>P, $F |- $G" ML {* structure T_Prover = Modal_ProverFun ( val rewrite_rls = thms "rewrite_rls" val safe_rls = thms "safe_rls" val unsafe_rls = thms "unsafe_rls" @ [thm "boxR", thm "diaL"] val bound_rls = thms "bound_rls" @ [thm "boxL", thm "diaR"] val aside_rls = [thm "lstar0", thm "lstar1", thm "lstar2", thm "rstar0", thm "rstar1", thm "rstar2"] ) *} method_setup T_solve = {* Scan.succeed (K (SIMPLE_METHOD (T_Prover.solve_tac 2))) *} "T solver" (* Theorems of system T from Hughes and Cresswell and Hailpern, LNCS 129 *) lemma "|- []P --> P" by T_solve lemma "|- [](P-->Q) --> ([]P-->[]Q)" by T_solve (* normality*) lemma "|- (P--<Q) --> []P --> []Q" by T_solve lemma "|- P --> <>P" by T_solve lemma "|- [](P & Q) <-> []P & []Q" by T_solve lemma "|- <>(P | Q) <-> <>P | <>Q" by T_solve lemma "|- [](P<->Q) <-> (P>-<Q)" by T_solve lemma "|- <>(P-->Q) <-> ([]P--><>Q)" by T_solve lemma "|- []P <-> ~<>(~P)" by T_solve lemma "|- [](~P) <-> ~<>P" by T_solve lemma "|- ~[]P <-> <>(~P)" by T_solve lemma "|- [][]P <-> ~<><>(~P)" by T_solve lemma "|- ~<>(P | Q) <-> ~<>P & ~<>Q" by T_solve lemma "|- []P | []Q --> [](P | Q)" by T_solve lemma "|- <>(P & Q) --> <>P & <>Q" by T_solve lemma "|- [](P | Q) --> []P | <>Q" by T_solve lemma "|- <>P & []Q --> <>(P & Q)" by T_solve lemma "|- [](P | Q) --> <>P | []Q" by T_solve lemma "|- <>(P-->(Q & R)) --> ([]P --> <>Q) & ([]P--><>R)" by T_solve lemma "|- (P--<Q) & (Q--<R) --> (P--<R)" by T_solve lemma "|- []P --> <>Q --> <>(P & Q)" by T_solve end